Kritik Sosial Dalam Karikatur Serangan Idf Terhadap Rumah Sakit As-Syifa Palestina - An shori, Alam; Hasanah, Ummi; Jambak, Melinda Raswari; Wargadinata, Wildana (Jurnal Media dan Komunikasi Indonesia, 2024)
The IDF raid on As-Syifa hospital is a serious matter because it is related to international humanitarian rules regarding civilian objects. Emad Hajjaj in his Instagram account criticizes this behavior with a caricature. This study aims to (1) reveal the representation of social criticism in Emad Hajjaj's caricatures on Instagram and (2) reveal the factors behind the making of caricatures. Primary data sources come from two caricatures in Emad Hajjaj's Instagram account, while secondary data come from books, journals, news, and articles relevant to this study. This type of research is qualitative research using the semiotic approach of Roman Jakobson's perspective. The data collection techniques used are screenshots, reading, and notes. The data analysis technique uses the Miles and Huberman technique which consists of data reduction, data presentation, and conclusion drawing. The result of this study is that researchers succeeded in revealing the forms of political criticism contained in two caricatures uploaded by @hajjaj_cartoons with six elements in the form of sender, context, contact, code, message and recipient. Meanwhile, the background of the criticism is a response to the IDF's actions.